2019
DOI: 10.1016/j.jcot.2018.10.002
|View full text |Cite|
|
Sign up to set email alerts
|

Bone block procedures for glenohumeral joint instability

Abstract: Glenoid bone loss is a well established cause of instability and long term morbidity if not adequadely addressed. Anterior glenohumeral instability due an anterior glenoid defect is significantly more common, and for many years has been well treated with open anterior bone block augmentation procedures, most commonly the latarjet procedure. However, with refinement of this technique and some interest in reducing morbidity associated with iliac crest bone harvest, arthroscopic bone block procedures with allogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…With the better understanding of the role of "engaging" Hill-Sachs lesions in glenohumeral biomechanics and the specific indications for bone-block glenoid reconstruction, in combination with the use of meticulous preoperative planning, advanced imaging (3D reconstruction) of the glenohumeral bone defects, minimally invasive surgical techniques, sophisticated implants, and individualized evidence-based rehabilitation protocols, glenoid bone block augmentation surgery has rapidly evolved over the last few years [30]. Although a number of studies have been recently published in the literature, none of the previous reviews examined in a systematic manner the outcomes of contemporary-only iliac crest bone block techniques [17,31,32]. To address this point, we conducted a systematic review of contemporary literature including publications from the last 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…With the better understanding of the role of "engaging" Hill-Sachs lesions in glenohumeral biomechanics and the specific indications for bone-block glenoid reconstruction, in combination with the use of meticulous preoperative planning, advanced imaging (3D reconstruction) of the glenohumeral bone defects, minimally invasive surgical techniques, sophisticated implants, and individualized evidence-based rehabilitation protocols, glenoid bone block augmentation surgery has rapidly evolved over the last few years [30]. Although a number of studies have been recently published in the literature, none of the previous reviews examined in a systematic manner the outcomes of contemporary-only iliac crest bone block techniques [17,31,32]. To address this point, we conducted a systematic review of contemporary literature including publications from the last 12 years.…”
Section: Discussionmentioning
confidence: 99%
“… 106 Seven of 11 had recurrent instability and 4 patients had a recurrent episode of dislocation. However, other literature demonstrates positive outcomes after shorter follow-up 92 with one study by Schwartz et al showing a significant improvement in Rowe score and Walch-Duplay score from 18.4 to 82.1 points and 37.4 to 82.9 points, respectively (P <0.01). 107 …”
Section: Anterior/posterior Bone Graftingmentioning
confidence: 93%
“…Complications after anterior or posterior glenoid bone grafting include hardware failure, painful hardware, osteoarthritis, 92 donor site pain (if autograft was harvested), 105 and specifically brachial plexus injury in anterior bone graft placement. 100 Kowalski et al demonstrated in a large Pearldiver database study that both anterior and posterior glenoid bone graft had an overall complication rate (dislocation, closed adhesion release, or reoperation) of approximately 20%, which was significantly greater than Bankart repair.…”
Section: Anterior/posterior Bone Graftingmentioning
confidence: 99%
“…Failure is defined by the presence of defects greater than 15% to 20%, 3 but ‘’subcritical’’ bone loss is also associated with a subjective feeling of instability and poorer results 4 . Although anatomical and nonanatomical bone graft reconstruction have been used for the treatment of these cases, most of these techniques use metal implants for fixation, independent of the graft used 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17. Bone resorption and residual pain are considered to be closely related to the absence of a sufficiently stable graft fixation and the presence of metal implants 18, 19, 20…”
mentioning
confidence: 99%